2020
DOI: 10.2147/copd.s250746
|View full text |Cite
|
Sign up to set email alerts
|

<p>Thoracic Imaging at Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review</p>

Abstract: Exacerbations of chronic obstructive pulmonary disease (COPD) are currently diagnosed based on changes in respiratory symptoms. Characterizing the imaging manifestation of exacerbations could be useful for objective diagnosis of exacerbations in the clinic and clinical trials, as well as provide a mechanism for monitoring exacerbation treatment and recovery. In this systematic review, we employed a comprehensive search across three databases (Medline, EMBASE, Web of Science) to identify studies that performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…As previously reported by our group, the magnitude of resistive load and the time frame used in our animal model were chosen to mimic the mechanical consequences observed in exacerbations of obstructive pulmonary diseases. 9,15,19 Indeed, there are human clinical data on the consequences of COPD exacerbations that are consistent with our findings, mainly from imaging studies, 31 since obtaining histological samples or performing lung permeability studies during acute exacerbation of COPD is challenging. In an autopsy study where in 6 patients death was attributed to respiratory failure secondary to COPD exacerbation per se, 3 of these patients were exhibiting bilateral infiltrates and 2 vascular congestion on the chest x-ray on Hospital admission.…”
Section: Discussionsupporting
confidence: 87%
“…As previously reported by our group, the magnitude of resistive load and the time frame used in our animal model were chosen to mimic the mechanical consequences observed in exacerbations of obstructive pulmonary diseases. 9,15,19 Indeed, there are human clinical data on the consequences of COPD exacerbations that are consistent with our findings, mainly from imaging studies, 31 since obtaining histological samples or performing lung permeability studies during acute exacerbation of COPD is challenging. In an autopsy study where in 6 patients death was attributed to respiratory failure secondary to COPD exacerbation per se, 3 of these patients were exhibiting bilateral infiltrates and 2 vascular congestion on the chest x-ray on Hospital admission.…”
Section: Discussionsupporting
confidence: 87%
“…In an attempt to standardize semi-quantitative clinical assessment of COPD and harmonize it with published data on quantitative computed tomography (QCT) phenotypes, a statement of the Fleischner Society proposed a visual CT based classification system comprised by five different emphysema predominant subtypes and two distinct airway predominant subtypes, and identified this proposal as a work in progress to drive future research, including outcomes of distinct CT phenotypes. 12,13 CT-based investigation has also demonstrated that the lung manifests divergent responses to noxious insults such as chronic tobacco smoke exposure. Smokers may appear resilient to the injurious effects of tobacco smoke or may develop emphysema and even pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chest X-ray is used frequently 29–31 despite evidence showing that it rarely alters 30 clinical management. Research on the value of a CT of the chest during HECOPD is ongoing; 32 whilst the relative infeasibility of CT scans likely contributed to strongly polarised views on its importance at time of HECOPD.…”
Section: Discussionmentioning
confidence: 99%